Skin color of Chinese women across different regions of China: An analysis based on both individual typology angle and hue angle - Sen Hou; Anzhang Li (Journal of Dermatologic Science and Cosmetic Technology, 2024)
Skin color is considered an important beauty standard for women in China. The typical tool for skin color measurement, individual typology angle (ITA), was developed based on Caucasian skin features. The ITA effectively measures the brightness of facial skin, which is traditionally associated with beauty in Caucasian women. However, in Chinese women, whiteness is not the only determinant of skin esthetics, and other elements such as “yellowness” and “redness” are also important considerations. Thus, the hue angle system was developed based on the skin features of Chinese women, whose skin is typically on the “yellow-red” spectrum. Studies examining the skin color of Chinese women based on both the ITA and hue angle should be carried out. The skin colors of 4500 women aged 18–45 years across five different regions of China were measured using both the ITA and hue angle systems. The relationship of the “red pigment and melanin content” with the “brightness and redness of skin color” was also examined. Further, the different skin types of women across different regions were identified. Measurements based on the ITA system reveal a saddle-shaped distribution of skin brightness among Chinese women across five different regions, with skin brightness being high in the east-west regions and low in the north-south regions. The ITA and hab values are not consistent in individual women, and thus, both need to be considered when evaluating skin color. Additionally, no correlation between the skin’s red pigment and melanin content and the skin’s ITA and hab values is identified. This study provides skin color data based on both the ITA and hue angle systems. The findings show that skin ITA/hab values cannot simply be explained by the red pigment/melanin content of the skin. Given the distribution of skin types across different regions of China, whitening ingredients causing little to no irritation should be used to formulate whitening cosmetics.